ORGANIZATIONALLY ECONOMIC FACTORS INCREASE THE EFFICIENCY OF THE ENTERPRISE - Matchanov Azamat Abadovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the problem of increasing the efficiency of the enterprise. Where are the main indicators that affect the economic efficiency of the organization, ways of increasing the indicators of economic efficiency are proposed.